Birth Outcomes in Women Who Have Taken Hydroxycholoroquine During Pregnancy: A Prospective Cohort Study. Issue 4 (10th March 2022) - Chambers, Christina D.; Johnson, Diana L.; Xu, Ronghui; Luo, Yunjun; Felix, Robert; Fine, Minh; Lessard, Chloe; Adam, Margaret P.; Braddock, Stephen R.; Robinson, Luther K.; Burke, Leah; Jones, Kenneth Lyons; et al.
Abstract : Objective: Findings from previous small studies have been reassuring regarding the safety of treatment with hydroxychloroquine (HCQ) during pregnancy. In one recent study, it was demonstrated that the frequency of major birth defects was increased in women who had received HCQ at a dose of ≥400 mg/day during pregnancy. This study was undertaken to examine pregnancy outcomes among women following the use of HCQ. Methods: The study cohort comprised pregnant women who were prospectively enrolled in the MotherToBaby/Organization of Teratology Information Specialists Autoimmune Diseases in Pregnancy Study and were receiving treatment with HCQ. For the control groups, disease‐matched women without HCQ exposure and healthy women were randomly selected from the same source, with subject matching using a 1:1 ratio. Data were collected through interviews, medical records, and dysmorphology examinations. Pregnancy outcome measures included the presence or absence of major and minor birth defects, rates of spontaneous abortion, rates of preterm delivery, and infant growth measures. Results: Between 2004 and 2018, 837 pregnant women met the criteria for study inclusion, including 279 women exposed to HCQ during pregnancy and 279 women in each unexposed control group. Sixty pregnant women (7.2%) were lost to follow‐up. Among the women with live births, major birth defects occurred as a pregnancy outcome in 20 (8.6%) of 232 women with HCQ exposure in the first trimester, compared to 19 (7.4%) of 256 disease‐matched unexposed controls (odds ratio [OR] 1.18, 95% confidence interval [95% CI] 0.61–2.26) and 13 (5.4%) of 239 healthy controls (adjusted OR 0.76, 95% CI 0.28–2.05). Risks did not differ in women who were receiving an HCQ dose of ≥400 mg/day. No pattern of birth defects was identified. There were no differences in the rates of spontaneous abortion or preterm delivery between groups. Occurrence of infant growth deficiencies did not differ in the HCQ‐exposed group compared to the disease‐matched unexposed control group, except in the infant's head circumference at birth (adjusted OR 1.85, 95% CI 1.07–3.20). Conclusion: In this study, there was no evidence of an increased risk of structural birth defects or other adverse outcomes among women receiving HCQ during pregnancy, with the exception of infant head circumference at birth. For pregnant women being treated with HCQ, these findings are reassuring.